Intellectual freedom and alternative priorities in library and information science research: A longitudinal study. (October 2022) - Gardner, Gabriel J
This article presents a bibliometric analysis of the library and information science literature to trace the emphasis that intellectual freedom and neutrality have received relative to an index of alternative and possibly competing topics. Emphasis is captured longitudinally by recording the number of results for various search terms associated with intellectual freedom, neutrality, diversity, equity, and inclusion in Web of Science from 1993 through 2020 and Library, Information Science and Technology Abstracts from 1970 through 2020. The results show that the number of works mentioning intellectual freedom and neutrality has increased only slightly over the study period, in sharp contrast to many entries on the diversity, equity, and inclusion index. With research interests being partially indicative of personal beliefs and professional activity, the impact of this relative change in emphasis on professional practice is discussed. Public controversies regarding library neutrality, intellectual freedom, and freedom of expression in libraries are summarized.